PENERAPAN STRATEGI TALKING STICK PADA SISWA SD UNTUK MENINGKATKAN AKTIVITAS BELAJAR IPS - Tawari, Iswan E; Saleh, Sufri (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The purpose of this study was to improve the activity and learning outcomes of social studies through the application of the Talking Stick strategy to fifth grade students of SD Negeri 14 Ternate City in the 2024/2025 Academic Year. This type of research is Classroom Action Research. The subjects in this study were teachers and 32 fifth grade students. The data collection method in this study used observation, testing, documentation and interview methods. Data analysis techniques in this study include: data collection, data reduction, data presentation, drawing conclusions. The results of this study indicate that student learning activities have increased from before the implementation of the action to the implementation of cycle II, the second meeting from 7 students (22%) to 30 students (94%) who expressed their opinions. From 7 students (22%) to 26 students (81%) who actively asked questions. From 9 students (28%) to 28 students (87%) who actively discussed. From 9 students (28%) to 26 students (81%) who listened to the explanation. From 11 students (34%) to 28 students (87%) who answered questions. Meanwhile, in terms of student learning outcomes, the learning outcomes before the action was carried out were 8 students (25%) until the second meeting of cycle II became 29 students (91%). The conclusions obtained in this study are as follows: the application of the Talking Stick learning strategy can improve learning activities and learning outcomes in the Social Studies subject of Class V Students of SD Negeri 14 Kota Ternate in the 2024/2025 Academic Year